Divergent and Concise Syntheses of Spiroisoxazolines: First Total Synthesis of 11‐Deoxyfistularin‐3. Issue 23 (14th July 2015) - Das, Prasanta; Hamme II, Ashton T.
Abstract: A divergent and concise base‐promoted Dieckmann‐type keto‐ester condensation strategy is demonstrated to generate two unique spiro[cyclohexadiene‐isoxazoline] moieties. The consecutive di‐bromination–elimination–bromination of the corresponding spiro moiety has been successfully utilized to furnish the desired core structure of many bromotyrosine derived spiroisoxazoline natural products. The spiroisoxazoline acid was further coupled with the desired diamine to accomplish the first total synthesis of 11‐deoxyfistularin‐3. This strategy could serve as an efficient alternative to previously developed oxidative dearomatizing spirocyclization of phenol as the essential step to synthesize this class of natural products. Abstract : A complementary route for spiroisoxazolines leads to the total synthesis of 11‐deoxyfistularin‐3.